Individualised or liberal red blood cell transfusion after cardiac surgery: a randomised controlled trial. (January 2022) - Fischer, Marc-Olivier; Guinot, Pierre-Grégoire; Debroczi, Stéphane; Huette, Pierre; Beyls, Christophe; Babatasi, Gérard; Bafi, Kevin; Guilbart, Mathieu; Caus, Thierry; Lorne, Emmanuel; Dupont, Hervé; Hanouz, Jean-Luc; et al.
Abstract: Background: Current practice guidelines for red blood cell (RBC) transfusion in ICUs are based on haemoglobin threshold, without consideration of oxygen delivery or consumption. We aimed to evaluate an individual physiological threshold-guided by central venous oxygen saturation S c vO 2 . Methods: In a randomised study in two French academic hospitals, 164 patients who were admitted to ICU after cardiac surgery with postoperative haemoglobin <9 g dl −1 were randomised to receive a transfusion with one unit of RBCs (haemoglobin group) or transfusion only if the S c vO 2 was <70% (individualised group). The primary outcome was the number of subjects receiving at least one unit of RBCs. The secondary composite outcome was acute kidney injury, stroke, myocardial infarction, acute heart failure, mesenteric ischaemia, or in-hospital mortality. One- and 6-month mortality were evaluated during follow-up. Results: The primary outcome was observed for 80 of 80 subjects (100%) in the haemoglobin group and in 61 of 77 patients (79%) in the individualised group (absolute risk –21% [–32.0; –14.0]; P <0.001). There was no significant difference in the secondary outcome between the two groups. Follow-up showed a non-significant difference in mortality at 1 and 6 months. Conclusions: An individualised strategy based on an central venous oxygen saturation threshold of 70% allows for a more restrictive red blood cell transfusion strategy with no incidence on postoperative morbidity or 6-month mortality. Clinical trial registration: NCT02963883 .